REFUSAL STRATEGIES USED BY MALAY ESL STUDENTSAND ENGLISH NATIVE SPEAKERS TO REFUSE A REQUEST - Norma Saad; Siti Jamilah Bidin; Ahmad Affendi Shabdin (Proceedings of The ICECRS, 2016)
The present study investigates similarities and differences of a speech act of refusal in English as realized by Malay Speakers of English (MSE) and Native Speakers of English (NSE). The study examined the types and also the contents of the strategies used by the two groups when refusing a request made by a higher status interlocutor. An Enhanced Open Role-play was utilized to obtain data on the types and content of refusal strategies. Participants of the study comprised 12 MSE undergraduate students from a local university and 12 NSE who were IGSCE and Diploma Baccalaureate students from an international school who had refused to the higher status interlocutor’s request. Qualitative data analytic methods were used to analyse the data which were classified into semantic refusal strategies and politeness strategies. Brown’s and Levinson’s politeness theory, Hofstede’s cultural dimensions and Hall’s high- and low-context cultures were used to guide the study. The findings revealed that the two groups shared many similarities in terms of types and contents of the strategies when refusing to the higher status interlocutor’s requests. Nevertheless, the NSE demonstrated a higher use of direct strategies and the content of their indirect strategies and adjuncts to refusal strategies reflect the western individualistic values. The MSEs,’ on the other hand exhibited the eastern values which prioritize group’s importance. These findings provide further insights on the complexities of refusal interaction and the patterns could be used by English language teachers as pragmatic input to develop English as a Second Language students’ ability to use socially appropriate language for the situation they encounter.